Implementation Of E-Open Application As A Strategic Innovation Of Public Services In The Pandemic Covid 19 Era In Bekasi - Susi Dian Rahayu; Ainur Rofieq; Nurul Aini; Arifudin Arifudin (VERITAS, 2023)
The COVID-19 pandemic that has hit almost the entire world, including Indonesia, has affected all aspects of life, one of which is in public services. The government has issued a policy for the entire community so that every activity is carried out online or online to prevent the spread of COVID-19 cases. By keeping up with the times and advancing technology, all parties, especially the government, must innovate to encourage more effective and efficient public services. This prompted the Bekasi City Disdukcapil to create an application-based innovation called e-OPEN. This study discusses how to implement the implementation of e-Open in population services in Bekasi City. The method used in this research is descriptive qualitative method, data collection is done by observation and literature study. Based on the results of the research conducted, the e-Open application belonging to the Bekasi City Disdukcapil is considered to be quite effective and easily accepted by the public. Because with this application, people who are busy can manage their population data easily and can be accessed anytime and anywhere. Through the Halo Pamor menu, people who have limitations in using the application also feel helped by the presence of the prestige task force.